Psychosocial Profiles among Persons with Substance Use Disorder Undergoing Islamic-Based Inabah Program in Kelantan, Malaysia. Issue 3 (3rd July 2018) - Lua, Pei Lin; Ahmad Nasrulddin, Nor Afiqah; Mohamad, Abdul Manam; Makhtar, Mokhairi; Jusoh, Julaily Aida; Abdullah, Ramle; Hassan, Azmi
ABSTRACT: Psychosocial profiles among a convenience sample of 37 Malay Muslim participants of Inabah program were measured using the Psychological Measure of Islamic Religiousness (PMIR). Data were analysed using SPSS 23.0. Positive relations with others emerged as the best-scored subscale whereas anger trait and depressed mood were minimal. Single and divorced respondents demonstrated significantly higher score for purpose in life. More favorable social desirability was reported by participants with no previous treatment. Less anger and depression were expressed by those not detained before. Essentially, psychosocial status of persons with substance use disorder undergoing Inabah program was moderate with some influences of sociodemographic factors.